1993
DOI: 10.1136/bmj.306.6883.956
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraception and risk of a cerebral thromboembolic attack: results of a case-control study.

Abstract: Objective-To assess the risk ofcerebral thromboembolism in women using low dose oral contraceptives.Design-A retrospective case-control study.Setting-All Danish medical, neurological, neurosurgical, and gynaecological departments.Subjects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(109 citation statements)
references
References 38 publications
2
103
0
4
Order By: Relevance
“…We included only 6 case-control studies. 18,[21][22][23][24][25] Characteristics of the included studies are summarizing in the Table. Four of them were carried out in Europe, 21,22,24,25 one in the United States, 23 and one worldwide. 18 Stroke was documented and diagnosed with clinical and radiological tools.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included only 6 case-control studies. 18,[21][22][23][24][25] Characteristics of the included studies are summarizing in the Table. Four of them were carried out in Europe, 21,22,24,25 one in the United States, 23 and one worldwide. 18 Stroke was documented and diagnosed with clinical and radiological tools.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies dealt with ischemic stroke, 22,24,25 whereas the others provided data on both ischemic and hemorrhagic strokes. 18,21,23 Participants' age in the included articles ranged from 15 to 44 years old, and controls were matched for age. The number of subjects varied across the studies (from 26 to 1828 for cases and from 224 to 5334 for controls).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies of second-generation oral contraceptives containing lower doses of estrogens did not find an increased risk of stroke. [242][243][244][245][246] However, one study did report an increased risk of stroke in women using first-, second-, or third-generation oral contraceptives. 247 The reasons for this discrepancy are not certain.…”
Section: Oral Contraceptive Usementioning
confidence: 99%
“…[8][9] As low-dose OCs became widely used, studies indicated a lower thrombotic risk. [21][22][23] It is now generally accepted that the use of low-dose OCs decreases the thrombotic risk compared with higher-dose compounds. This finding is particularly true for deep vein thrombosis 22,24 but may not be as well defined for arterial events such as stroke and myocardial infarction.…”
Section: Ocs and Thrombosismentioning
confidence: 99%